Rethinking relationships in the construction industry: integrating sustainable development into project management processes - Eid, Mohamed El Mohamandy (University of Edinburgh, 2004)
We live in a time of threat from human induced climate change. The challenges we now face are greater than ever; global environmental degradation, economic turbulence, widespread social exclusion and inequalities have now elevated the problem from a national level to a global scale. This thesis discusses these challenges in terms of the performance of the construction industry. The research addresses four main pillars: the Construction Industry, Sustainable Development, Project Management and Systems Thinking. It examines the notions of each topic individually then exhibits the interconnections between the four subjects. The arguments of this research propose integrating Sustainable Development, Project Management and Construction through a Systems Thinking approach as a facilitating tool of incorporation. SUSTAINABLE DEVELOPMENT is a dynamic process, which simultaneously protects and enhances the global ecosystem while working on three parallel levels; social, environmental and economic. It also systematically integrates vital environmental and social guidelines into economic development, financial planning and general management activities. THE CONSTRUCTION INDUSTRY is a major economic activity within developed countries and an emerging key market for developing countries. Its size and pervasiveness are critical factors in a successful strategy for sustainable development. The construction industry in particular, recognises the importance of 'PROJECT MANAGEMENT' to the successful completion of complex undertakings. As a growing profession, project management provides an opportunity to achieve project targets with higher quality standards of delivery within the foreseen time frame, budget and cost. On the basis of the previous definitions, the research examines the notions of sustainable construction as a process that promotes affordable solutions to the problems of the built environment and the significant impact it has environmentally, economically and socially. The proposition of a systematic SUSTAINABLE APPROACH TO PROJECT MANAGEMENT PROCESSES assumes critical significance in the process of the integration in question. The main objective of this research is to demonstrate that the implementation of sustainable development guidelines into the project management processes for construction projects, will allow a better performance for sustainable construction practices. When approached in terms of 'systems thinking' theories, this allows the integration to occur with a holistic approach to the existing relationships but with more significant impacts on the processes and outcomes of the systems. Thinking and acting sustainably requires not only incremental change but a revolution in approach, a shift of perspective which will need to be reflected in future generations of management techniques. The research methodology relies on a synthesiso f comprehensivea nd assessedli terature reviews of the construction industry, sustainable development, project management and systems thinking and their interrelationships. The integration is then examined through suggested sets of arguments underpinned with analysis of the potential opportunities for rethinking the relationships through three proposed case studies. A further examining methodology relies on an online questionnaire which facilitated the consultation with academics, researchers, professionals and practitioners in the field of construction, project management and sustainability. The general outcomes of the research demonstrate that sustainable project management processes are possible to achieve and manifest their positive impact on changing the policies, strategies and standards that normally guide the performance of construction projects. Individuals have a right, a role and a responsibility to contribute to the promotion and application of sustainable development. This research is a step forward for the project management profession to contribute a high standard of sustainable strategies to construction projects while it also calls for further work to be done on the application of the proposed integration on real life projects to assess, quantify and measure the outcomes on construction processesT. his does not limit the arguments to the construction industry but indeed calls for further testing on other industries which contribute to the built environment and ultimately to a better quality of life.
Keywords: Culture; Environment; Construction industry